2006
DOI: 10.1007/s10734-004-6377-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Students’ Personality Characteristics, Self-Perceived Competence and Learning Conceptions in the Acquisition and Development of Social Communicative Competence: A Longitudinal Study

Abstract: An important purpose of higher social work education is to guide students to acquire and develop social-communicative competencies. The purpose of this study was to investigate the role students' personality characteristics, self-perceived communicative competence and learning conceptions play in the acquisition and development of social-communicative competencies. We designed and tested a hypothetical model on the student-related variables -self-perceived communicative competence, learning conceptions and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 60 publications
4
11
0
1
Order By: Relevance
“…Cronbach's alpha scores for the other subscales are comparable to those reported by Bakx et al (2003Bakx et al ( , 2006 and reflect high reliability.…”
Section: Research Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Cronbach's alpha scores for the other subscales are comparable to those reported by Bakx et al (2003Bakx et al ( , 2006 and reflect high reliability.…”
Section: Research Resultssupporting
confidence: 58%
“…Since learning conceptions are to a certain degree context-dependent, it is relevant to take the knowledge domain into account when studying learning conceptions (Bakx, Van der Sanden, Sijtsma, Croon & Vermetten, 2006;Eklund, 1998;Vermunt & Vermetten, 2004). Pintrich (2003) has emphasized the central role of motivation when investigating learning and teaching.…”
Section: Person: Student Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such beliefs can have a significant impact upon the way we think and learn (Hofer, 2002;Bakx, VanDer Sanden, Sijtsma, Croon, & Vermetten, 2006). Hofer and Pintrich (1997) suggested that the nature of knowledge has two dimensions, i.e., the certainty of knowledge, and the simplicity of knowledge.…”
Section: Epistemological Belief Systemsmentioning
confidence: 99%
“…Social skills are defined as the ability to behave in accordance with the requirements of the social context in which the interpersonal relationship occurs (Alber, Heward, 1996;Bakx et al, 2006). The components of social skills are: social competence, being flexible within a context, being target-oriented, and possessing intra-and inter-personal characteristics (Bakx et al, 2006;Schlundt & McFall, 1985). Social competence, empathy, and communication skills are part of the social development of preservice teachers (Ergül et al, 2013;Zwaans, ten Dama, &Volman, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%